The role that nature conservation can play to mitigate the spread of future infectious diseases - Tonelli, Mattia; Lobo, Jorge; Benedetti, Yanina; Morelli, Federico; Verdú, José (European Journal of Ecology, 2021)
The emergence of infectious diseases is reviewed highlighting the potential role played by main environmental anthropogenic disturbances as, deforestation, land-use change, human-induced climate change, biodiversity loss and the illegal wildlife trade. Ultimately, it is plausible that the human impact on the biosphere could be the root cause of these emerging diseases, and that economic globalization, population growth and landscape anthropization might increase the likelihood of the emergence of novel zoonoses. This pattern bears similarities to phenomena that occurred during the Neolithic period with the emergence of agriculture and cattle domestication. Still today such phenomena could be accelerated by the vastly increased traffic of people and goods. Finally, we argue in favour of strong policies and actions aiming to mitigate the human impact on natural ecosystems as a key strategy to prevent future zoonoses.